Phytochrome A Mediates the Disassembly of Processing Bodies in Far-Red Light - Schwenk, Philipp; Hiltbrunner, Andreas (Frontiers in Plant Science, 2022)
Phytochromes are red- and far-red light receptors that control the growth and development of plants, enabling them to respond adequately to changing light conditions. It has been shown that halted mRNAs stored in RNA granules called processing bodies are released upon light perception and contribute to the adaptation to the light environment. However, the photophysiological background of this process is largely unknown. We found that light of different wavelengths can trigger the disassembly of processing bodies in a dose- and time-dependent manner. We show that phytochromes control this process in red- and far-red light, and that cytoplasmic phytochrome A is sufficient and necessary for the far-red light-induced disassembly of processing bodies. This adds a novel, unexpected cytoplasmic function to the processes controlled by phytochrome A. Overall, our findings suggest a role of phytochromes in the control of translationally halted mRNAs that are stored in processing bodies. We expect our findings to facilitate understanding of how light and environmental cues control the assembly and disassembly of processing bodies, which could have broader implications for the regulation of non-membranous organelles in general.